Republic Of Estonia : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2001)
This report on the Observance of Standards and Codes on Data Module is a summary assessment of Estonia's data practices against the IMF's Special Data Dissemination Standard, complemented by an in-depth assessment of the dimensions of data quality that underlie the national accounts, consumer prices, government finance, monetary, and balance-of-payments statistics. Accuracy and reliability are generally good, but could be improved in a few areas of national accounts and in general government data by strengthening source data and improving statistical techniques.